2008
DOI: 10.1161/strokeaha.107.504779
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Gait-Related Improvements After Therapist- Versus Robotic-Assisted Locomotor Training in Subjects With Chronic Stroke

Abstract: Background and Purpose-Locomotor training (LT) using a treadmill can improve walking ability over conventional rehabilitation in individuals with hemiparesis, although the personnel requirements often necessary to provide LT may limit its application. Robotic devices that provide consistent symmetrical assistance have been developed to facilitate LT, although their effectiveness in improving locomotor ability has not been well established. Methods-Forty-eight ambulatory chronic stroke survivors stratified by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
403
5
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(446 citation statements)
references
References 48 publications
17
403
5
12
Order By: Relevance
“…The Lokomat gait orthosis provides the advantage of reducing the burden on clinical staff during weight-supported gait training and has been found by some researchers to have advantages over conventional therapies [50][51]. By addressing important psychological aspects of mental engagement in technology-assisted therapies, innovations may be made that help bridge the gap found by some researchers with conventional therapies [52][53]. Our approach might help to improve some of the features of technology-assisted rehabilitation-taking a step toward meeting more of the needs of the patient and therapist.…”
Section: Resultsmentioning
confidence: 99%
“…The Lokomat gait orthosis provides the advantage of reducing the burden on clinical staff during weight-supported gait training and has been found by some researchers to have advantages over conventional therapies [50][51]. By addressing important psychological aspects of mental engagement in technology-assisted therapies, innovations may be made that help bridge the gap found by some researchers with conventional therapies [52][53]. Our approach might help to improve some of the features of technology-assisted rehabilitation-taking a step toward meeting more of the needs of the patient and therapist.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, learning in TIFT was disjointed early in the training, with subjects often hitting the path walls, stopping and trying several strategies before determining the correct shoulder-elbow coordination needed to advance within the path. Nevertheless, for stroke rehabilitation, we believe further study into assistance modes such as TIFT is needed, given the recent negative findings in robots that have used the TD training mode [42][43] and the evidence that passive movement training does not improve motor control [82][83]. For example, Bluteau et al found that in a drawing task, haptic guidance with a position-based controller similar to our TD training mode was inferior to a force-based controller for motor learning [84].…”
Section: Discussionmentioning
confidence: 83%
“…A recent multisite clinical trial of several upper-limb robots found them comparable to dose-matched conventional therapy, but superior to usual and customary care in motor function scales at 36 weeks [41]. In contrast, two recent clinical trials of lower-limb robots found them inferior to conventional methods [42][43]. This finding suggests that the type of robot and the control modes used do affect outcome, and further studies are needed to optimize robotic approaches to movement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Hidler et al [13] also conducted a multicenter randomized trial that investigated the usefulness of Lokomat robot-assisted therapy in 72 patients with subacute stroke and found less effective in the 6-minute walk test (6MWT) and Functional Ambulation Category (FAC) tests than the conventional gait training. Similarly, Hornby et al [12] found that Lokomat robot-assisted therapy in 62 patients with chronic stroke was not superior to the conventional gait training. Such inconsistent results in the Lokomat robot-assisted studies may result from different experimental design and testing methods utilized [10], lack of volitional neuromuscular control [14], restricted pelvic and trunk movement control [15,16], arm swing, as well as altered acceleration and deceleration from pre-swing to initial contact [17].…”
Section: End-effector Type Of Robot-assisted Gait Trainingmentioning
confidence: 94%
“…Mayr et al [10] and Husemann et al [11] reported greater augmented effects from combined exoskeleton robot-assisted gait training combined with conventional gait training compared with conventional gait training alone in 10 subacute stroke patients. Hornby et al [12] conducted a randomized controlled study that compared the effects of exoskeleton robot-assisted gait training and manual facilitation using an assistas-needed paradigm on gait function in patients with chronic stroke. Moreover, Hidler et al [13] also conducted a multicenter randomized trial that investigated the usefulness of Lokomat robot-assisted therapy in 72 patients with subacute stroke and found less effective in the 6-minute walk test (6MWT) and Functional Ambulation Category (FAC) tests than the conventional gait training.…”
Section: End-effector Type Of Robot-assisted Gait Trainingmentioning
confidence: 99%